The Job Resilience of Indonesian Migrant Workers in Taiwan in Terms of Motivation and Social Support - Nasir, Sri Astuti; Iswardhani, Indri; Nulthazam, Sarah; Sandira, Nur Fadilah Ayu; rostina, Rostina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Work Resilience of Indonesian Migrant Workers in Taiwan Based on Motivation and Social Support). Work resilience of Indonesian domestic migrant workers has become a significant issue in the dynamics of cross-border employment, particularly in Taiwan. This study aims to explore the interrelation between work motivation, social support, and work resilience in the lived experiences of Indonesian domestic migrant workers. A descriptive qualitative approach was employed through a single case study using in-depth online interviews with one informant who has worked in Taiwan for nearly six years. The primary data were supported by secondary sources, including scholarly journals and official reports.The findings reveal that work motivation—both intrinsic and developed through work experiences such as improved soft skills—serves as a key driver in building individual resilience. Social support from family, migrant communities, and employers provides emotional strength and practical resources that enhance the workers’ ability to cope with physical and psychological pressures. Moreover, positive relationships with employers and trust in carrying out responsibilities contribute to a sense of competence and self-confidence. Institutional support from the government through agencies such as BP2MI also underpins worker protection and resilience. This study concludes that the work resilience of migrant workers is shaped by the synergy between strong internal motivation and the presence of social support in various forms.